Internalization of Values Four Corners In Educational Leadership towards Affirming the Pancasila Student Profile - Nurdin, Hisosiyan; Aqilah, Nur; B, Anatasia.; Alwi, Muhammad (International Journal of Education, Information Technology, and Others, 2024)
This study discusses "The Internalization of Sulapa Eppa Values in Educational Leadership for Affirming the Profile of Pancasila Students." It is based on the cultural values or local wisdom held by the Bugis-Makassar community, known as "Sulapa Eppa Values." The research employs a literature review method, which is classified as qualitative descriptive research derived from the issue being studied. The aim of this research is to understand how the role or internalization of these Sulapa Eppa values in educational leadership influences the output related to the Pancasila Student Profile. The results show that the internalization of Sulapa Eppa values in educational leadership can contribute to the formation of students' better personalities by instilling Sulapa Eppa values, namely Macca (Wisdom), Malempu' (Honesty), Warani (Courage), and Magetteng (Consistency). The application of Sulapa Eppa values, which are closely related to human values, greatly influences the standpoint of a leader. Thus, this research is expected to provide deeper insight into the importance of integrating local values into the education system and their impact on shaping students' character in accordance with Pancasila values.